2017
DOI: 10.1186/s12950-017-0160-9
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width (RDW) as a biomarker for respiratory failure in a pediatric ICU

Abstract: BackgroundThe red cell distribution width (RDW) is a widely available, inexpensive, and highly reproducible test that reflects the range of the red cell sizes. Any process that releases reticulocytes in the circulation will result in an increase in RDW. Elevated RDW values are linked to worsened pulmonary function in the adult population. We performed a retrospective cohort study to describe the association between RDW and respiratory failure in critically ill children in a in a pediatric intensive care unit (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 28 publications
0
28
0
5
Order By: Relevance
“…RDW, one of the numbers or blood cell indices, reflects the variation in the size of RBC (red blood cells), which has been tightly correlated with critical disease [10][11][12] but negligent in COVID-19. It is a robust predictor of the risk of all cause patient mortality and bloodstream infection in the critically ill [11][12][13][14], including acute exacerbation of interstitial pneumonia, ARDS [10,15]. RDW also can predict prognosis of sepsis, which was tied to poor COVID-19 outcomes-death [16].…”
Section: Discussionmentioning
confidence: 99%
“…RDW, one of the numbers or blood cell indices, reflects the variation in the size of RBC (red blood cells), which has been tightly correlated with critical disease [10][11][12] but negligent in COVID-19. It is a robust predictor of the risk of all cause patient mortality and bloodstream infection in the critically ill [11][12][13][14], including acute exacerbation of interstitial pneumonia, ARDS [10,15]. RDW also can predict prognosis of sepsis, which was tied to poor COVID-19 outcomes-death [16].…”
Section: Discussionmentioning
confidence: 99%
“…1 However, many recent studies reported an association between elevated RDW and risk of mortality in different populations, such as elderly patients, 2 patients with coronary artery disease, 3,4 hemodialysis patients, 5 heart failure, 6 and ischemic stroke. 7,8 More recently, RDW was associated with increased short-term mortality in unselected critically ill patients, 9 in pediatric critically ill patients, 10 after cardiac arrest, 11 in septic patients, 12,13 or in those suffering from subarachnoid hemorrhage. 14 Moreover, in a retrospective study, RDW improved the prognostic performance of the Simplified Acute Physiology Score for both short-and long-term mortality in critically ill patients.…”
Section: Conclusion: Rbc Transfusion Significantly Increasedmentioning
confidence: 99%
“…More recently, RDW was associated with increased short‐term mortality in unselected critically ill patients, in pediatric critically ill patients, after cardiac arrest, in septic patients, or in those suffering from subarachnoid hemorrhage . Moreover, in a retrospective study, RDW improved the prognostic performance of the Simplified Acute Physiology Score for both short‐ and long‐term mortality in critically ill patients …”
mentioning
confidence: 95%
“…Red cell distribution width (RDW) is a widely used, inexpensive, and highly reproducible test that is automatically reported in the hemogram test, and which reflects the size distribution of circulating red blood cells. Any process that triggers the release of reticulocytes to circulation increases RDW . The acute systemic inflammatory response resulting from many different etiologies can affect both erythropoiesis and erythrocyte maturation.…”
mentioning
confidence: 99%
“…These studies have demonstrated the role of RDW in various inflammatory events and pathophysiological conditions such as septic shock, acute appendicitis, pulmonary disease, and cardiovascular disease . In addition, many studies suggest that RDW can be used as a useful biomarker for disease severity and clinical outcome evaluation in the critical patient group . But to the best of our knowledge, there is no study investigating the role of RDW in the severity assessment of childhood AGE.…”
mentioning
confidence: 99%